(untitled) (Epidemiology, Biostatistics, and Public Health, 2024)
In the latest edition of the Conference of the Parties (COP 28, Dubai, 2023), the discussion on air pollution-induced climate change was expanded to include for the first time the health concerns of exposed populations [1]. This fact enshrines the indissolubility of the three themes – Environment, Climate and Health – not only within the scientific community, but also in political, educational and dissemination contexts.